Perbaikan Keseimbangan Lintasan Lini Produksi Dengan Metode Ranked Positional Weight (RPW) untuk Meningkatkan Efisiensi - Christata, Bellachintya Reira; Majid, Syahrul; Asri, Vikha Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
XYZ is an electronics company that requires an efficient and timely production process to meet market demand. One way to increase production efficiency is to improve the production line. Currently the company is faced with production problems, namely the existence of unbalanced work groups which have a balance loss value of up to 61%. Therefore, this study tries to solve these problems using the RPW method. The RPW (Ranked Positional Weight) method is a track balancing method by establishing a work station based on the weight of each operation. Where the highest weight becomes the first order in the formation of work stations. From the results of calculations using the RPW, the number of work activity groupings is less, namely as many as 10 work stations. The work station generated using the RPW method has a track efficiency level of 96% with a balance delay value of 4%. This means that the grouping of proposed work activities has a more efficient trajectory balance than the previous grouping of work activities..